Justiça e moral no trabalho: vendedores do comércio varejista do Rio de Janeiro - Magaldi, Tiago (Universidade Federal de São Carlos, 2022)
This thesis describes and analyses the work of commission salesmen at a large Brazilian retailer, Via S.A. (Via Varejo), owner of the Casas Bahia and Ponto Frio chains, under the hypothesis that the set of experiences involved in this work would lead to the adoption of radically individualist criteria of distributive justice ("to each according to his abilities") and the critique of collectivist criteria ("to each according to the amount collectively produced, regardless of his individual contribution"). Based on interviews and non-participant observation, I describe the daily life of the salespeople, reconstructing the typical stages of sales interactions with customers, and of the relationships with managers and colleagues on the store floor, interactions that are closely related to the commission system of remuneration: a strongly variable system, which fluctuates according to the flow of customers, the individual ability of the salesperson, the different levels of goals set by the company, and even by the annual seasonality. Using data from RAIS and from the interviews, I also argue, contrary to the literature, that the occupation of salesperson does not, in practice, only include young workers with little roots in the commerce sector, being merely a "passing" occupation. The workers interviewed, on the contrary, have a long trajectory in commerce, so that it is possible to consider the decisive influence of this work on their living conditions and - what most interests this thesis - their subjectivity. Thus, I reconstruct the elements of an idealized occupational identity, built on the image of the salesperson as a comprehensive mediator between the customers' consumption needs and the products he or she has available, and analyse the criteria of distributive justice that underlie the legitimacy of the unequal distribution of remuneration and prestige on the store floor. I point out the criteria of "proportionality" and "merit" as hegemonic, enjoying wide legitimacy among salespeople, but not absolute: there are also criteria mobilized for criticism, such as retribution for effort, charging considered excessive and, above all, the requirement of a minimum level of distribution that legitimizes the inequality of results. The analysis of the critical manifestations to the company by the salesmen during the crisis offers another critical principle: that of the company's supposed duty of care to its "collaborators", in a denunciation that I called "paternalistic". I argue that the strength of the objective and subjective structure of the commissioned salesperson's work tends to produce individualistic criteria in the subjects, but that this process is not absolute, finding itself open to criticism that has the potential to delegitimize unequal distributive outcomes: there are limits to the adoption of individualistic criteria, and there is a pragmatic adaptation, on the part of the workers, of possible criticisms to real situations.
Justice and morality at work: retail salespeople in Rio de Janeiro
Keywords: Retail salesman; Retailers; Distributive justice; Identity; Variable pay; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS